Analisis Framing Kasus Korupsi Menteri Kominfo Johnny G Plate - Pangeran Bungsu, Agung; Muzakir, Fohan (Journal of Da'wah, 2023)
When corruption is mentioned in the news, nearly everyone in society pays attention. The media exerts the most power on how the subtleties of news building are enjoyed by the audience. Will the audience accept what is presented or the other way around. This article analyzes how Robert Entman constructed the news stories about the corruption case involving Johnny G. Plate, the minister of communication and information technology, and Surya Paloh, the National Democratic political party's secretary general, that appeared on the Tempo.co and Metro TV YouTube channels. Robert Entman's four framing arrangements came to the conclusion that because Tempo.co and Metro TV reported in divergent ways, the framing research was finally fully conclusive.